Training characteristics that stimulate essential training motivation and individual effectiveness: Analysing the Sample of Malaysian Public Sector using SEM-AMOS - Aziz, Siti Fardaniah Abdul; Ibrahim, Anesee (International Journal of Psychosocial Rehabilitation, 2020)
Training characteristics are very important to ensure training effectiveness; however, research explaining the right training characteristics affecting individual effectiveness is limited. Hence, this research was done to close the research gap by determining the effect of training characteristic on individual effectiveness by analysing essential training motivation as mediator. Data were analysed using SEM-AMOS among 203 Malaysian Public Service Officers attended training organized by The Malaysian National Institute of Public Administration in 2016. Findings indicated that majority respondents perceived the level of individual effectiveness as high. In addition, training content familiarity followed by training relevant, training design, and training reputation were important characteristics of a training program affecting individual effectiveness. Additionally, essential training motivation partially mediated the relationship between training characteristics and individual effectiveness. Significantly, research findings are important to determine the most important characteristic of training in human resource development to ensure employees’ individual effectiveness.